The Attitudes of Yemeni University Students towards the Use of Metacognitive Writing Strategies - Sultan, Mahmoud Kulaib Saeed; Al-Mekhlafi, Mohammed Abdu Ahmed (International Journal of Language and Literary Studies, 2025)
The present study aimed to investigate the Yemeni University students’ attitudes towards the use of the metacognitive strategies in an Academic Writing course. It also explored whether there was any significant differences in the students’ attitudes towards the metacognitive writing strategies based on their gender. This study employed a quantitative approach. The sample of the study consisted of thirty Second Level students (10 males and 20 females) who were studying English in the Department of English at the College of Languages at Sana’a University in Yemen during the academic year 2023- 2024. The researchers used a literature-based questionnaire with special reference to Rhema and Miliszewska (2017), Al Moqbali et al, (2020) and Ajayi (2024). It consisted of seventeen statements that aimed to measure the attitudes of the Yemeni students towards the use of the metacognitive strategies in the writing skill. The results of the present study showed that the total mean scores among the participants was (3.74), based on a five –points Likert scale ranging from 1- strongly agree to 5- strongly disagree. (1- strongly agree 2- agree 3- neutral 4- disagree 5- strongly disagree). The scores for each item ranged from 1-5. Furthermore, the findings of the study indicated that the majority of the students reported positive attitudes towards the use of the metacognitive strategies as they help to improve their writing skills. In addition, there was no statistically significant difference between the male and female students in their attitudes towards using the metacognitive strategies. This research ends up with some recommendations for the people concerned with the Yemeni teaching English as a foreign language (TEFL) and presents some suggestions for further studies.